An empirical analysis of the determinants of water demand in Italy. (1st September 2016) - Romano, Giulia; Salvati, Nicola; Guerrini, Andrea
Abstract: This paper investigated factors affecting household water consumption in major Italian towns. Specifically, water demand in 103 Italian towns was analyzed over a five-year period (i.e., 2007 to 2011). Data was collected from each towns on the potential determinants of water consumption, including tariffs, income per capita, weather conditions and geographical and population characteristics. Previously, it was unclear whether a larger presence of public ownership would lead to improved water conservation practices and reductions in water consumption. Consequently, in addition to more commonly studied variables, water utilities ownership was included as a factor that could affect household water consumption. A mixed-effects model was used that contained both fixed effects and random effects. The results of this study provided interesting insights into the factors driving residential water consumption. The results confirmed that an applied tariff had a negative effect on residential water consumption. Further, the data showed that towns with larger populations served had higher levels of consumption. In relation to climatic and geographical features, only altitude exerted a significant negative effect on water consumption and temperature and precipitation had no effect on demand. Income per capita was also found not to have a significant effect on water consumption. The results of the study confirmed that water utilities ownership did not have a significant effect on water consumption. Tariffs were found to be significantly lower in towns where the water service was managed by publicly owned water utilities and, thus, water consumption in these towns was higher. Highlights: The paper investigated the factors affecting household water consumption in Italy. Applied tariff had a negative effect on residential water consumption. Altitude exerted a negative effect on demand while climate did not influence demand. Tariffs were lower where the water service was managed by publicly owned utilities. Consumption was higher if the water service was managed by publicly owned utilities.